Philosophy for architects. - Mitrović, Branko (New York : Princeton architectural press, 2011)
Introduction ## Plato ## Aristotle ## The rise of modernity ## Immanuel Kant ## Romanticism and historicism ## Phenomenology and hermeneutics ## Philosophes and philosophers ## Analytic philosophy ## Conclusion.
boek